2002
DOI: 10.1161/01.str.0000027440.68031.b0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Depolarization of Cerebellar Granule Neurons by Specific Inhibition of TASK-1

Abstract: Background and Purpose-The mechanisms underlying neuronal excitotoxicity during hypoxic/ischemic episodes are not fully understood. One feature of such insults is a rapid and transient depolarization of central neurons. TASK-1, an open rectifying K ϩ leak channel, is significant in setting the resting membrane potential of rat cerebellar granule neurons by mediating a standing outward K ϩ current. In this study we investigate the theory that the transient neuronal depolarization seen during hypoxia is due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 24 publications
2
73
0
3
Order By: Relevance
“…Thus, increased I Na may be self-limiting (or protective) if it leads to membrane depolarization, inducing Na V channel inactivation and, thereby, limits subsequent Na + flux. Consistent with this notion, we previously found that acute hypoxic challenge induces membrane depolarization when rat CGN were studied in current-clamp mode (Plant et al, 2002). Indeed, chronic stressors that increase the level of SUMOylated proteins in cells (Shao et al, 2004), including the transcription factor HIF1a (Cheng et al, 2007), and modify global patterns of SUMOylation (Cimarosti et al, 2012) have been inferred to be cytoprotective in cases where gene regulation and protein turnover are altered to conserve energy (Henley et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Thus, increased I Na may be self-limiting (or protective) if it leads to membrane depolarization, inducing Na V channel inactivation and, thereby, limits subsequent Na + flux. Consistent with this notion, we previously found that acute hypoxic challenge induces membrane depolarization when rat CGN were studied in current-clamp mode (Plant et al, 2002). Indeed, chronic stressors that increase the level of SUMOylated proteins in cells (Shao et al, 2004), including the transcription factor HIF1a (Cheng et al, 2007), and modify global patterns of SUMOylation (Cimarosti et al, 2012) have been inferred to be cytoprotective in cases where gene regulation and protein turnover are altered to conserve energy (Henley et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Because parallel fibers are rich in Na V 1.2 channels, our studies may underestimate the effects of Na V 1.2-SUMOylation in response to hypoxia in the cerebellum. Moreover, we employ standard, potassium-free, recording solutions to study I Na and, therefore, I Kso , a rat CGN current we previously showed to be responsive to hypoxia (Plant et al, 2002), was not evaluated in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that lack of oxygen may lead to depolarization and reduced levels of oxygen may lead to partial depolarization. Studies have shown that hypoxia leads to depolarization in different types of rat cells [73,74], as well as depolarization of mitochondria [75,76]. This hypoxic depolarization of mitochondria appears to be caused by decreased electron transport chain activity due to lack of oxygen [76].…”
Section: Influence Of Respiration On the Cellular Levelmentioning
confidence: 99%